Comparative dental anatomy in Disaster Victim Identification: Lessons from the 2009 Victorian Bushfires - Lain, Russell; Taylor, Jane; Croker, Sarah; Craig, Pamela; Graham, Jeremy (Forensic science international, 2011)
In the Disaster Victim Identification (DVI) response to the recent bushfire disasters in rural Victoria, Australia, forensic odontology played a significant role in the identification process. Particular features of this disaster were challenging to the odontologists. A characteristic of house fires is the extended time period during which the remains may be subject to heat, and their subsequent disruption as buildings collapse. This can result in dislodgement of teeth from sockets, loss of tooth crowns from roots, disruption of anatomical location of teeth and damage to bony features. Commingling of human remains also is often a feature, as is commingling of animal remains with human. Two cases which illustrate these features are described. A strategy for improving familiarity with comparative dental anatomy and improving skills in dental anatomy is suggested.